Comparative study of beliefs about causes of mental illness in a clinically depressed and non-clinical population - Amarasuriya, Santushi D. (My University, 2010)
In determining the applicability of western theoretical models of mental illness in Sri Lanka, this study examines whether beliefs about causation of mental illness, focusing on Depression, of a clinically depressed and non-clinical Sri Lankan population mapped onto conceptualisations of causation found in these western models. It examines if significant differences in such beliefs exist between the populations studied, and also according to gender, age and education. Beliefs were examined using a Sinhala adaptation of the Opinions about Psychological Problems Questionnaire comprising subscales representing psychodynamic, Cognitive, Humanistic, Behavioural, Organic, Socioeconomic and Naive causal models, amongst a purposive, clinically depressed sample of 31 clients and an equal non-clinical sample matched for gender, age, and education. Beliefs about causation reliably mapped onto these models except for the Naive Model. Positive correlation between models was seen, with higher correlation between psychologically-oriented models. Both samples agreed with the Psychodynamic and Cognitive models. There were significant differences in agreement with most models between the samples with greater orientation towards agreement in the non-clinical sample. No significant differences were found according to gender and age but were seen for education in two subscale models